Who participates in global governance? : states, bureaucracies, and NGOs in the United Nations - Ruhlman, Molly A. (London : Routledge, 2015)
'Why are non-state actors (NSAs) sometimes granted participation rights in International Organizations and what influences the decision? This work presents the case that that non-state actors have lobbied for formal participation roles in international organizations since at least the formation of the United Nations system but formal upstream participation roles are uncommon. Secretariats consistently support partnership with NSAs in implementation as a means towards greater efficiency or efficacy, and states consistently support such partnerships as launched by the secretariat as a means towards fulfilling the IO's intended mission. However, states and their IOs have more often than not raised opposition to granting NSAs a right of participation in member-state assemblies during decision-making. They have instead favoured informal means of consultation. During those occasions in which NSAs have been granted a formal right of participation during decision-making they have demonstrated the ability to supply specific benefits to IOs or to particular member-states who then support NSA participation rights. States and their organizations have consistently considered the formal inclusion of NSAs and chosen when, where, and in what ways to allow such inclusion in a manner that furthers the interests of individual states and their multilateral organizations. Challenging the regular assumption that the power of states and the efficacy of multilateral governance have simply wilted in the heat of globalization while NSAs have flourished, this work features analysis of key institutions such as UNCEF, UNDP and the Environment Programme. It will be of great interest to students and scholars of international relations, the United Nations, and NGOs.'--
1. Who participates, and who decides? International organizations as complex actors -- 2. Mobilizing public opinion : NGOs and the United Nations -- 3. Non-state actors and UNICEF -- 4. Non-state actors and the UN Development Programme -- 5. Non-state actors and the UN Environment Programme -- 6. Interests and participation in multilateralism : seeking innovation amidst stubborn interests.
Includes bibliographical references and index.
Mode of access : World Wide Web.
Keywords: United Nations -- Membership; Non-governmental organizations; Globalization -- Political aspects